Macula-Off Retinal Detachment with Refractory Macular Hole Previously Closed with Autologous Platelet-Rich Plasma: A Case Report - Gugliemo Parisi; Federico Ricardi; Giacomo Boscia; Andrea Ghilardi; Francesco Gelormini; Paola Marolo; Matteo Fallico; Sergio D'Antico; Marika Salafia; Michele Reibaldi (Case Reports in Ophthalmology, 2023)
The purpose of this report was to present a case of a refractory full-thickness macular hole (FTMH) complicated with recurrent retinal detachment (RD) previously treated with an autologous platelet-rich plasma (aPRP) plug. A 65-year-old male patient presented to our department with a FTMH, RD, and a giant retinal break. Preoperative best corrected visual acuity (BCVA) was 1.40 logMAR (20/500). A 25-G pars plana vitrectomy (PPV) was performed, with peripheral retinal-breaks laser barrage, peeling of the internal limiting membrane, and silicon oil injection. One month later, spectral domain optical coherence tomography (SD-OCT) showed the persistence of the FTMH with a diameter of 712 μm. Therefore, the patient underwent silicon oil removal and aPRP injection with good anatomical outcome and improvement of BCVA to 0.6 log-MAR (20/80). Two months later a recurrence of macula-off RD was detected, but SD-OCT showed that the aPRP plug was still in place and kept the two margins of the macular hole together. The patient underwent a further PPV with silicon oil injection and subsequent silicon oil removal with no postoperative complications. Two months later, the retina remained attached, SD-OCT confirmed FTMH closure and BCVA was 0.52 logMAR (20/63). In conclusion, this case report aims to underline the remarkable efficacy of aPRP in promoting FTMH closure, which was maintained despite subsequent recurrence of macula-off RD.